Existence Of Company Size In Control Towards Family Ownership And Debt Policy Value Of Companies - Murtiadi Awaluddin; Alim Sholihin; Sumarlin Sumarlin; Rulyanti Susi Wardhani; Andi Sylvana (Integrated Journal of Business and Economics (IJBE), 2020)
This study aims to examine the effect of family ownership, debt policy on firm value with firm size as a control variable. The sample used was a family company listed on the Indonesia Stock Exchange from 2014 to December 2017. The type of this research was quantitative using Agency theory and Signaling Theory. Analysis technique with multiple regression analysis. The results showed that family ownership had a positive and significant effect on firm value, and debt policy had a negative and significant effect on firm value. While company size as a control variable in this study cannot control the relationship of the influence of family ownership and debt policy on firm value, in other words, company size as a control variable does not have a significant effect on the relationship of family ownership and corporate value policy debt.